Three Years Experience of Inguinal Hernia in Children in BSMMU (Journal of Paediatric Surgeons of Bangladesh, 2016)
Objective: The aim of this study is to evaluate the management of inguinal hernias in children as a day case surgery in elective basis.Methods: From July 2011 to June 2014, 141 infants and children with inguinal hernias were seen, operated on, and followed up as outpatient procedure in the Department of Paediatric Surgery of Bangabandhu Sheikh Mujib Medical University Dhaka, Bangladesh (BSMMU) Age, sex, side of hernia, presence of an associated hydrocele/ undescended testes/ VPshunt, occurrence of contralateral hernia, clinical aspects of these patients, type of surgery, mortality, and mobidity were studiedResults: The ages ranged from 2months to 14 years (mean age, 6.28 years) with a male-to female ratio of 3:1. There were 59.6% right, 34.8% left, and 5.7% bilateral hernias (all are indirect variety).The most common associated anomaly was hydrocele in 29(20.8%)patients, undescended testis in 9(6.5%) patients and in 4(2.8%) patients had ventriculoperitoneal shunt. The content of the hernial sac in 56(39.7%) patients were omentum and next were intestine in 30(21.3%) patients. Overall, there were 13 (9.2%) sliding hernias. Among them in five case of boys four (80%) patients contents were cecum and one (20%) patient was sigmoid colon. In case of girls, contents were ovaries in all eight patients. Contralateral groin exploration was not done of any patients at the initial hernia repair. There were recurrences in 2(1.4%) patients, 13(9%) patients developed wound infections, and 21(15%) patients had scrotal haematocele. There were no postoperative deaths. A contralateral hernia developed in three (2%) children within one year after the initial repair.Conclusions: Inguinal hernia is a common surgical condition in children. Elective surgery is associated with minimal morbidity. A routine contralateral groin exploration is not done at the initial hernia repairJ. Paediatr. Surg. Bangladesh 6(2): 34-38, 2015 (July)